2020
DOI: 10.5114/aoms.2020.98815
|View full text |Cite
|
Sign up to set email alerts
|

Expression pattern of circulating long non-coding RNA GAS5 as a novel biomarker in non-small cell lung cancer patients

Abstract: IntroductionThe finding that long noncoding RNAs (lncRNAs) originating from tumor cells could be found in general circulation has prompted the idea to use lncRNAs as noninvasive diagnostic biomarkers of particular diseases. In this study we explored the expression pattern of circulating GAS5 (growth arrest-specific transcript 5) lncRNA in non-small cell lung cancer (NSCLC) patients and its association with clinicopathological characteristics.Material and methodsExpression pattern of circulating GAS5 was analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…The primary applications for ddPCR are rare allele detection in heterogeneous samples like liquid biopsies or FFPE samples of solid tumors, non-invasive prenatal diagnostics, viral load detection, gene expression and copy number variation, single cell gene expression profiling, and the validation of low-frequency mutations identified by sequencing analysis. Moreover, epigenomic markers originating from tumor cells could be analyzed (methylation sites, circulating regulatory RNAs) [ 72 ]. A good agreement between BEAMing and ddPCR has been shown, with a kappa value of 0.91 (95% CI: 0.85–0.95) [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…The primary applications for ddPCR are rare allele detection in heterogeneous samples like liquid biopsies or FFPE samples of solid tumors, non-invasive prenatal diagnostics, viral load detection, gene expression and copy number variation, single cell gene expression profiling, and the validation of low-frequency mutations identified by sequencing analysis. Moreover, epigenomic markers originating from tumor cells could be analyzed (methylation sites, circulating regulatory RNAs) [ 72 ]. A good agreement between BEAMing and ddPCR has been shown, with a kappa value of 0.91 (95% CI: 0.85–0.95) [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, more attention is directed to examine the impact of long noncoding RNAs (lncRNAs) on cancer pathology [8][9][10] . Long non-coding RNAs, often called "Genomic Dark Matter", are non-protein-coding transcripts with length of more than 200 nucleotides.…”
Section: Introductionmentioning
confidence: 99%
“…They can also interact with promoter or enhancer sequences to modulate gene expression and consequently, act as tumor suppressors or oncogenes [10][11][12][13] . The finding that lncRNAs originating from tumor cells can be detected in the plasma has prompted the idea to use lncRNAs as biomarkers in cancer patients 9 . Indeed, accumulated knowledge on lncRNAs have indicated their possible usage as diagnostic/prognostic markers and also as therapeutic targets in many tumors 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to studying the role of GAS5 in the pathogenesis of cancer, its potential role as a prognostic marker was also investigated. In numerous types of cancer, it has been shown that reduced GAS5 expression was associated with unfavorable clinical and pathological characteristics related to advanced stages of the disease, making it a marker for poor prognosis [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%